Synthesis, structure characterization and quantum chemical study on relationship between structure and antioxidant properties of novel Schiff bases bearing (thio)/carbohydrazones - Muğlu, Halit; Yakan, Hasan; Misbah, Amhimmid Ghayth Amhimmid; Çavuş, M. Serdar; Bakır, Temel Kan (Springer Science and Business Media LLC, 2021)
A series of novel isatin-based Schiff base derivatives, namely β-isatin aldehyde-N,N′-(thio)/carbohydrazone derivatives (1–8), have been synthesized. All of the compounds were purified, and IR, 1H NMR and 13C NMR spectroscopic methods and elemental analysis were used to characterize the compounds. Moreover, the in vitro antioxidant activity of the compounds was evaluated by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging method and compared with standard natural antioxidant, gallic acid. Experimental data were supported by density functional theory (DFT) calculations. B3LYP hybrid functional with 6–311 +  + g(2d,2p) basis set was used to calculate ground-state geometries, FMO energies and related chemical reactivity parameters of the compounds. In addition to the structural and spectral analysis calculations of the compounds, NBO, QTAIM, NCI, Fukui and DOS analyses were also performed at the same level of theory, and the data were used to determine the effects of conformational and electronic properties of substitute groups in the reactive regions of the compounds on the reaction with DPPH and to analyze the antioxidant behavior of the compounds. New Schiff bases bearing (thio)/carbohydrazone and isatin were synthesized. Structures of synthesized compounds were elucidated using spectroscopic techniques. Antioxidant activities of the compounds were measured by DPPH method. FMO energies, NBO, QTAIM, NCI, Fukui and DOS analyses were used to examine the relationship between the electronic properties and antioxidant activity.
Keywords: 3. Good health